Who lost Russia? an enquiry into the failure of the Russian-Western partnership - Eyal, Jonathan (Whitehall paper series, 2009)
An enlarged NATO, forced to consider how to defend its new members from possible Russian aggression, is set for an 'unavoidable clash' of interests with Russia transfixed by Cold War logic that still harbours 'imperial ambitions'. In this report, Dr Eyal challenges the growing consensus that the West is responsible for missing a historic opportunity to engage Russia, by allegedly failing to appreciate the full depth of Russia's aspirations and feelings.